Disruption of thrombo-inflammatory response and activation of a distinct cytokine cluster after subarachnoid hemorrhage. (November 2018) - Savarraj, Jude PJ; McGuire, Mary F; Parsha, Kaushik; Hergenroeder, Georgene; Bajgur, Suhas; Ahn, Sungho; Zhu, Liang; Espino, Elena; Chang, Tiffany; Blackburn, Spiros; Kim, Dong H; Dash, Pramod; et al.
Highlights: Cytokines involved in inflammatory and thrombotic processes are elevated after SAH. Positive correlations between the processes were observed in SAH and UA. Negative correlations between the processes were present in UA but absent in SAH. A growth colony stimulating factor cluster was unique in SAH. Abstract: Background: Unregulated inflammatory and thrombotic responses have been proposed to be important causes of early brain injury and worse clinical outcomes after subarachnoid hemorrhage (SAH). Objective: We hypothesize that SAH is characterized by an increased inflammatory and thrombotic state and disruption of associations between these states. Methods: This is a retrospective cohort study of 60 patients with SAH. 23 patients with unruptured aneurysms (UA) and 77 patients with traumatic brain injury (TBI) were chosen as controls. Plasma cytokine levels were measured using a 41-plex human immunoassay kit, and cytokine patterns associated with SAH, UA and TBI were identified using statistical and informatics methods. Results: SAH was characterized by an increase in several cytokines and chemokines, platelet-derived factors, and growth factors. Cluster analysis identified several cytokine clusters common in SAH, UA and TBI groups – generally grouped as platelet-derived, vascular and pro-inflammatory clusters. In the UA group, the platelet-derived cluster had an inverse relationship with the inflammatory cluster which was absent in SAH. Additionally, a cluster comprising of growth and colony stimulating factors was unique to SAH. Conclusions: A cluster of cytokines involved in growth and colony stimulation was unique to SAH. Negative associations between the thrombotic and inflammatory molecules were observed in UA but not in SAH. Further studies to examine the pathophysiology behind the cluster unique to SAH and the associations between the thrombotic and inflammatory cytokines are required.